Achieving Dependability in Service-Oriented Systems - Xu, Jie (Dependable and Historic Computing, 2011)
Service-orientation is a useful means of developing highly flexible and adaptive software systems, and it is a paradigm that has been increasingly adopted into Grids and Clouds. However, service-oriented architectures and designs also bring with them new challenges in the fields of dependability and security that need to be addressed carefully in order to provide sufficient support to enable service-oriented systems to offer non-trivial Quality of Service guarantees. In this paper we examine such challenges and introduce several advanced techniques developed at the University of Leeds to achieve dependability and security in service-oriented systems and applications. These techniques include schemes for achieving fault tolerance, privacy protection, and dynamic authentication, as well as a method for assessing dependability based on fault-injection. We describe and discuss each technique alongside the results of experimental evaluations of it.